2013
DOI: 10.1002/ggge.20127
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Cenozoic low‐Ca alkaline basalts in the Nanjing basaltic field, eastern China: The case for mantle xenolith‐magma interaction

Abstract: [1] Although peridotite xenoliths are common in alkaline basalts, it is still unclear whether the chemical compositions of their host rocks have been affected by these mantle fragments and, if so, what processes are involved in this alteration of the host basalts. Here, we document a kind of xenolith-rich alkaline basalts from the Nanjing basaltic field, eastern China. These basalts contain lower concentrations of CaO (4.1-7.8 wt %) and Sc (3.3-17.8 ppm) and have lower Ca/Al (0.3-0.6) and higher Na/Ti ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 91 publications
0
15
0
3
Order By: Relevance
“…Data for Cenozoic basalts in Eastern China are shown for comparison (NE China: Basu et al, ; Chu et al, ; Kuritani et al, ; Liu, Chen, et al, ; Rasskazov et al, ; Sun, Teng, et al, ; Sun et al, ; Wang et al, ; Yan & Zhao, ; Yan et al, ; Zhang et al, ; Zhang et al, ; Zhao et al, ; Zou et al, ; Zou et al, . North China: Basu et al, ; Chen et al, ; Choi et al, ; Guo et al, ; Han et al, ; Ho et al, ; Li, Ma, et al, ; Wang et al, ; Xu et al, ; Yu et al, ; Zeng et al, ; Zhang et al, ; Zhang et al, ; Zou et al, . South China: Li, Xu, et al, ; Yu et al, ; Ho et al, ; Huang et al, ; Sun et al, ; Zeng et al, ; Zou et al, ), including data for the Chaihe basalts (big gray dots; Ho et al, ; Li, Ma, et al, ; Zhao & Fan, ; Xue et al, ).…”
Section: Whole‐rock Compositions Of the Huihe Nephelinitesmentioning
confidence: 99%
“…Data for Cenozoic basalts in Eastern China are shown for comparison (NE China: Basu et al, ; Chu et al, ; Kuritani et al, ; Liu, Chen, et al, ; Rasskazov et al, ; Sun, Teng, et al, ; Sun et al, ; Wang et al, ; Yan & Zhao, ; Yan et al, ; Zhang et al, ; Zhang et al, ; Zhao et al, ; Zou et al, ; Zou et al, . North China: Basu et al, ; Chen et al, ; Choi et al, ; Guo et al, ; Han et al, ; Ho et al, ; Li, Ma, et al, ; Wang et al, ; Xu et al, ; Yu et al, ; Zeng et al, ; Zhang et al, ; Zhang et al, ; Zou et al, . South China: Li, Xu, et al, ; Yu et al, ; Ho et al, ; Huang et al, ; Sun et al, ; Zeng et al, ; Zou et al, ), including data for the Chaihe basalts (big gray dots; Ho et al, ; Li, Ma, et al, ; Zhao & Fan, ; Xue et al, ).…”
Section: Whole‐rock Compositions Of the Huihe Nephelinitesmentioning
confidence: 99%
“…Experimental studies have confirmed that reaction between a siliceous melt and peridotite produces silica‐undersaturated alkali melts owing to the formation of orthopyroxene and/or garnet at the expense of olivine [ Mallik and Dasgupta , , , ], where the degree of alkalinity and silica undersaturation of the resulting melt increase with increasing system CO 2 content [ Mallik and Dasgupta , ]. Despite abundant evidence that melt‐rock interaction occurs in the shallow mantle and contributes to the compositional diversity of intraplate basalt [ Xu et al ., ; Søager and Holm , ; Zeng et al ., ; Liu et al ., ], it is still not well understood how these reactions and thus the erupted basalt compositions spatially and temporally evolve, which we do in this contribution.…”
Section: Introductionmentioning
confidence: 99%
“…The most important controls on the compositional diversity are inferred to be heterogeneous mantle sources with variable amounts of recycled crustal components and/or variable degrees of mantle partial melting [ Hofmann and White , ; McKenzie and O'Nions , ; Weaver , ; Hofmann , , ; Sobolev et al ., , ; Willbold and Stracke , , ; Walter et al ., , ; Stracke , ]. In addition to source heterogeneity, interaction between mantle‐derived melt and surrounding rocks during ascent may also contribute to the compositional diversity of the erupted magma [ Wagner and Grove , ; Xu et al ., ; Tang et al ., ; Lambart et al ., ; Mallik and Dasgupta , , , ; Søager et al ., ; Zeng et al ., ; Mallik et al ., ; Liu et al ., ]. Interaction between asthenosphere‐derived alkali‐rich melt and refractory lithospheric mantle has, for example, been proposed to explain the high SiO 2 and Cr and low Al 2 O 3 and CaO content, and the “kinked” REE patterns of Hawaiian [ Wagner and Grove , ] and Datong [ Xu et al ., ] tholeiitic basalt, reflecting the crystallization of olivine and the consumption of orthopyroxene in melt‐rock reactions.…”
Section: Introductionmentioning
confidence: 99%
“…(), s Zeng et al . (), t Webb et al . (), u Vasilieva (), v Petrov (), w Kuznetsova and Chumakova ().…”
Section: Resultsunclassified